China's health care system reform: Progress and prospects. (14th June 2017) - Li, Ling; Fu, Hongqiao
Summary: This paper discusses the progress and prospects of China's complex health care reform beginning in 2009. The Chinese government's undertaking of systemic reform has achieved laudable achievements, including the expansion of social health insurance, the reform of public hospitals, and the strengthening of primary care. An innovative policy tool in China, policy experimentation under hierarchy, played an important role in facilitating these achievements. However, China still faces gaps and challenges in creating a single payer system, restructuring the public hospitals, and establishing an integrated delivery system. Recently, China issued the 13th 5‐year plan for medical reform, setting forth the goals, policy priorities, and strategies for health reform in the following 5 years. Moreover, the Chinese government announced the "Healthy China 2030" blueprint in October 2016, which has the goals of providing universal health security for all citizens by 2030. By examining these policy priorities against the existing gaps and challenges, we conclude that China's health care reform is heading in the right direction. To effectively implement these policies, we recommend that China should take advantage of policy experimentation to mobilize bottom‐up initiatives and encourage innovations.